Gut Microbiota and Gut-Brain Axis in Health and Disease A Narrative Review - Wasiak, Jakub; Zielonka, Kacper; Dądela, Bartosz; Markowski, Marcin; Śliwa, Natalia; Majewska, Emilia Maria; Kawalska, Eliza; Gnitecki, Szymon; Janczura, Szymon; Borowski, Maciej (Quality in Sport, 2025)
Microbiota, a composition of trillions of microorganisms, plays essential roles in metabolism, immunity, and gut-brain axis connection. It helps in the digestion and production of valuable metabolites and keeps intestinal integrity intact. A balanced microbiota or eubiosis supports health; dysbiosis causes leaky gut syndrome, systemic inflammation, and chronic diseases. Therefore, the purpose of this review is to provide an analysis of the microbiota-gut-brain axis (GBA), as well as important microbial metabolites like trimethylamine N-oxide (TMAO), short chain fatty acids (SCFAs), and their implications concerning health and disease states. A comprehensive search of references related to microbiota was conducted on PubMed using the following search terms: “microbiota, gut-brain axis, dysbiosis, eubiosis, microbiota composition, microbial metabolites”. Major metabolites such as SCFAs help with the regulation of immune functions, act as protectors of the blood-brain barrier, and are known to support neuroprotection, while deleterious substances such as TMAO find association with cardiovascular diseases. Dysbiosis in the gut finds association with various chronic diseases such as type 2 diabetes, hypertension, and neurodegenerative disorders. Changes in microbial composition disrupt metabolic processes and provoke systemic inflammation. A better understanding of these mechanisms would facilitate the early detection of diseases based on the recognition of specific bacterial shifts and/or metabolite imbalances. Microbiota-health-improving relationships are still being explored, demonstrating the need for additional studies aimed at developments of specific treatments for disease prevention and treatment.